Obesity and C‐reactive protein in various populations: a systematic review and meta‐analysis. Issue 3 (22nd November 2012) - Choi, J.; Joseph, L.; Pilote, L.
Summary Obesity has been associated with elevated levels of C‐reactive protein (CRP), a marker of inflammation and predictor of cardiovascular risk. The objective of this systematic review and meta‐analysis was to estimate the associations between obesity and CRP according to sex, ethnicity and age. MEDLINE and EMBASE databases were searched through October 2011. Data from 51 cross‐sectional studies that used body mass index (BMI), waist circumference (WC) or waist‐to‐hip ratio (WHR) as measure of obesity were independently extracted by two reviewers and aggregated using random‐effects models. The Pearson correlation (r) for BMI and ln(CRP) was 0.36 (95% confidence interval [CI], 0.30–0.42) in adults and 0.37 (CI, 0.31–0.43) in children. In adults, r for BMI and ln(CRP) was greater in women than men by 0.24 (CI, 0.09–0.37), and greater in North Americans/Europeans than Asians by 0.15 (CI, 0–0.28), on average. In North American/European children, the sex difference in r for BMI and ln(CRP) was 0.01 (CI, −0.08 to 0.06). Although limited to anthropometric measures, we found similar results when WC and WHR were used in the analyses. Obesity is associated with elevated levels of CRP and the association is stronger in women and North Americans/Europeans. The sex difference only emerges in adulthood.